Diagnostic Modalities in Oral Pathology: Integrating Advance Diagnostic Techniques to Differentiate Malignant and Benign Lesions: Integrating Advanced Diagnostic Techniques to Malignant and Benign Lesions - Iqbal, Kanza; Fatima, Kanwal; Minhas, Madeeha; Siddiqui, Aman Ullah; Khizer, Bisma; Anique, Muhammad; Shah, Muhammad Arsalan (Pakistan Journal of Health Sciences, 2024)
Diagnosis and treatment planning in oral pathology is dependent on the differentiation of malignant from benign oral lesions. Clinical, radiographic and histopathological methods combined provide comprehensive diagnosis and patient care property. Objectives: To describe how the combined use of clinical assessments, imaging modalities and histopathological techniques can be used together to improve the differentiation of oral lesions between malignant and benign pathologies. Methods: In this paper, a systematic review was conducted using PRISMA guidelines. Studies published between January 2013 and April 2024 were searched from databases including PubMed, Google Scholar and Semantic Scholar. After the screening, 51 met the inclusion criteria from a total of 112 articles initially screened. Sixteen studies were ultimately analysed that examined oral pathology diagnostic advancements utilizing a combination of clinical, radiographic, and histo-chemo-pathological approaches. Results: Combining clinical examinations with imaging techniques such as cone beam computed tomography, and histopathological evaluations increases the accuracy of oral lesion diagnosis. The integrated approaches reveal malignancies earlier and reduce misdiagnoses. Histopathological analysis was shown to be the gold standard, but even this can be improved with additional clinical and radiographic data. Conclusions: It was concluded that accurate diagnosis and differentiation of benign vs. malign oral lesions requires the integration of clinical, radiographic, and histopathological methods. Such a multi-modal approach will support early detection and consequent tailored treatment strategies that maximise the patient outcome.